PERAN SERTIFIKAT TANAH WAKAF DALAM MENGATISIPASI DINAMIKA ZAMAN: STUDI KASUS MADRASAH DINIYAH MUAWANATUL MUSLIMIN DI KUDUS (ZISWAF: Jurnal Zakat dan Wakaf, 2016)
The existence of Islamic educational institutions of the Dutch colonial era to be the target because Islam has the spirit of colonialism visit, so that madrasas as a colonial threat. However, the Holy, Muslim leaders played a major role in realizing the existence of Islamic institutions with the aim of broadcasting Islam. Party contributing more important is muwakif (a pewakaf) land for Madrasah Diniyah Muawanatul Muslimin (madrasah Muawanah) so eksisnya sustainable educational institution since 1915 until now. One thing that should be examined administrators and organizers of educational institutions, namely evaluating soil perwakafan administration madrasas that later did not show up issues that do not make pleasant situation. It is necessary to involve the government, civil society and private citizens really materialized.